Immune cell counts and risks of respiratory infections among infants exposed pre- and postnatally to organochlorine compounds: a prospective study - Darnerud Per; Johannisson Anders; Aune Marie; Thuvander Ann; Glynn Anders; Ronquist Gunnar; Cnattingius Sven (BMC, 2008)
Abstract Background Early-life chemical exposure may influence immune system development, subsequently affecting child health. We investigated immunomodulatory potentials of polychlorinated biphenyls (PCBs) and p,p'-DDE in infants. Methods Prenatal exposure to PCBs and p,p'-DDE was estimated from maternal serum concentrations during pregnancy. Postnatal exposure was calculated from concentrations of the compounds in mother's milk, total number of nursing days, and percentage of full nursing each week during the 3 month nursing period. Number and types of infections among infants were registered by the mothers (N = 190). White blood cell counts (N = 86) and lymphocyte subsets (N = 52) were analyzed in a subgroup of infants at 3 months of age. Results Infants with the highest prenatal exposure to PCB congeners CB-28, CB-52 and CB-101 had an increased risk of respiratory infection during the study period. In contrast, the infection odds ratios (ORs) were highest among infants with the lowest prenatal mono-ortho PCB (CB-105, CB-118, CB-156, CB-167) and di-ortho PCB (CB-138, CB-153, CB-180) exposure, and postnatal mono- and di-ortho PCB, and p,p'-DDE exposure. Similar results were found for pre- and postnatal CB-153 exposure, a good marker for total PCB exposure. Altogether, a negative relationship was indicated between infections and total organochlorine compound exposure during the whole pre- and postnatal period. Prenatal exposure to CB-28, CB-52 and CB-101 was positively associated with numbers of lymphocytes and monocytes in infants 3 months after delivery. Prenatal exposure to p,p'-DDE was negatively associated with the percentage of eosinophils. No significant associations were found between PCB and p,p'-DDE exposure and numbers/percentages of lymphocyte subsets, after adjustment for potential confounders. Conclusion This hypothesis generating study suggests that background exposure to PCBs and p,p'-DDE early in life modulate immune system development. Strong correlations between mono- and di-ortho PCBs, and p,p'-DDE exposures make it difficult to identify the most important contributor to the suggested immunomodulation, and to separate effects due to pre- and postnatal exposure. The suggested PCB and p,p'-DDE modulation of infection risks may have consequences for the health development during childhood, since respiratory infections early in life may be risk factors for asthma and middle ear infections.